Research on measuring thermal conductivity of quartz and sapphire glass using rear-side photothermal deflection method - Kim, Gwantaek; Kim, Donghyuk; Kang, Sukkyung; Yoo, Jaisuk; Kim, Hyunjung (Applied Sciences (Switzerland), 2021)
As the display industry continues to advance, various new materials are being developed for utilizing microtechnology and nanotechnology in display panels. Among these, transparent materials have been widely applied to the internal wiring of displays and flexible substrates, owing to their high optical transmittance, isotropy, and anisotropy. Thus, measurement of the thermophysical properties of various transparent materials is important. This study measured thermal conductivity by selecting quartz, a transparent isotropic material, and sapphire glass, a transparent anisotropic material, as measurement target materials using a rear-side photothermal deflection method. Measurements were made via a three-dimensional unsteady heat conduction equation, to which complex transformation was applied and numerically analyzed using COMSOL Multiphysics. Phase delays for a pump beam and a probe beam for a relative position were derived through a deflection analysis. From the derived phase delays between the numerical analysis and experimental result with optical alignment, the absolute and relative errors of quartz were appropriately confirmed to be 0.069 W/m-K and 5%, respectively, while those of the sapphire glass were likewise confirmed to be 0.55 W/m-K and 1.5%, respectively.
Keywords: Anisotropic; Optical alignment rear-side deflection; Photothermal effect; Thermal conductivity